The use of Android Applications as an Effort to Implement Islamic Education to Overcome Family Disharmony: Penggunaan Aplikasi Android Sebagai Upaya Penerapan Pendidikan Islami Untuk Mengatasi Ketidakharmonisan Keluarga - Isroqunnajah; Muttaqin, M. Imamul; Ghaffar, Abdul; Munir, Misbah (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was first to determine the development of an application for early detection of non-medical diseases with the Quran system in the Tumpang Talun Blitar community. Second, knowing the application of non-medical detection applications with the Qur'ani system in cases of household disharmony. This type of research is a qualitative study with a phenomenological approach. Data analysis techniques: data collection stage, data reduction stage, data conclusion stage. Research Results Preparing the object of therapy, namely someone who is suspected of having a non-medical disorder, namely by means of mass filtering ruqyah. Displaying an android application screen that displays calligraphy of certain verses which have been explained in many hadiths and explanations of scholars' can keep Satan's interference away. After seeing the Android application, usually, someone will experience different reactions, there are screaming, crying, vomiting, burping, fainting, sweating, feeling sick in certain parts, and some are possessed. The next step is to sort and select non-medical cases that can affect household disharmony